Nutritional status and socio-demographic characteristics of the people of south-west coastal region in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Bangladesh is in danger area of the world because of its geographic location and the coastal zone of Bangladesh is worldwide recognized as an extremely vulnerable area. For determining disaster related losses and possible disaster management options, the south-west coastal belt Manirampur upazila and Abhaynagar upazila of Jessore district were selected. The survey was conducted by pre-structured questionnaire among six villages from Bagutia union of Abhaynagar upazila and Haridaskati union of Manirampur upazila, during January-June, 2015. A total of 100 households were randomly selected from the six study villages which were based on mainly livelihood pattern of the households (crop production, shrimp culture and others). The average income of the respondents was found 2001-4000 Tk. per month. Average land holding capacity per household was about 80 decimal. About 90% respondents of the study area said the intensity of disaster was more than before. Most of the respondents thought they were vulnerable to disaster. Most of the respondents were experienced with water logging condition. This study attempts to develop a proposed solution for enhancing DMS which reducing loss and copes with all kind of disaster in Bangladesh. In the study area 80% people to wanted TRM and 20% people do not want TRM; they thought TRM might be the probable solution of disaster vulnerability. It can be concluded that number of victim people caused by disaster decreases because of technological advancement but disaster occurrence increases from past to recent due to climate change impact.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 323-332